2014
DOI: 10.1063/1.4904143
|View full text |Cite
|
Sign up to set email alerts
|

Astrobiology: An astronomer's perspective

Abstract: Abstract. In this review we explore aspects of the field of astrobiology from an astronomical viewpoint. We therefore focus on the origin of life in the context of planetary formation, with additional emphasis on tracing the most abundant volatile elements, C, H, O, and N that are used by life on Earth. We first explore the history of life on our planet and outline the current state of our knowledge regarding the delivery of the C, H, O, N elements to the Earth. We then discuss how astronomers track the gaseou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 241 publications
0
4
0
Order By: Relevance
“…Deep in the cold miplane most molecules except H 2 , H + 3 and their isotopologs are frozen out onto the grains. There has been enormous observational and model activity in this field in recent years, see recent reviews 196,[216][217][218][219] . Highlights include the Spitzer and ground-based detections of hot (∼ 300 − 800 K) C 2 H 2 , HCN, H 2 O and CO 2 originating in the inner ∼1 AU of disks [220][221][222][223][224][225][226] .…”
Section: Protoplanetary Disksmentioning
confidence: 99%
“…Deep in the cold miplane most molecules except H 2 , H + 3 and their isotopologs are frozen out onto the grains. There has been enormous observational and model activity in this field in recent years, see recent reviews 196,[216][217][218][219] . Highlights include the Spitzer and ground-based detections of hot (∼ 300 − 800 K) C 2 H 2 , HCN, H 2 O and CO 2 originating in the inner ∼1 AU of disks [220][221][222][223][224][225][226] .…”
Section: Protoplanetary Disksmentioning
confidence: 99%
“…Nitrogen isotope fractionation is discussed in Section 4. More comprehensive reviews can be found in e.g., Caselli & Ceccarelli (2012), Bergin (2014), Ceccarelli et al (2014), and Willacy et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting planetary atmosphere will hence be extremely metal-poor in the first place. Late bombardment with left-over planetesimals [ 14 , 15 ] will cause an element re-enrichment leading once more to a change of the atmospheric composition. The opacity of the atmosphere surrounding the planetary core plays an important role for the critical mass that inhibits further accretion [ 16 ].…”
Section: Introductionmentioning
confidence: 99%